Security Analysis - Cottle Sidney (MC Graw Hill, 1988)
Since its publication,Security Analysis by Graham and Dodd has been the investment bible and has sold more than 750,000 copies. Now the fifth edition of this classic updates the application of the Graham and Dodd valuation approach for today's greatly changed investment environment.